Influence of transformational and transactional leadership on agile project success - Mohammad Ansari; Mahmoud Abouraia; Rania El Morsy; Venkat Ram Raj Thumiki (Project Leadership and Society (PLAS), 2024)
This study investigates the influence of Transformational and Transactional Leadership contribution in project accomplishment. It specifically evaluates the mediating role of Leadership for Agile project methodology. The data was collected from cross-sectional professionals such as Information Technology project Managers of various fields, Civil and Construction, Pharmaceuticals, Telecommunication, Higher Educational Institutions (HEIs) in Oman that comprised 384 valid samples. We used conformity factor analysis for reliability and validity of our measurement and it was valid and reliable. Partial Least-Squares Structural Equation Modelling (PLS-SEM) was used to analyze the theoretical framework. The results confirmed leadership enhances agile project methodology through the project excellence, improves end user satisfaction, value addition by achieving triple constraints. It was observed that leadership improves project performance in which team building, management commitment, unobstructed vision, daily standup meeting eases the influence of leadership on Agile methodologies.
Keywords: 650; Agile project methodology; Collaborative research; Multi-disciplinary; Project success criteria; Sustainability; Transformational and transactional leadership